2020
DOI: 10.1101/2020.08.07.241802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Epitope-based Malaria Vaccine Targeting the Junctional Domain of Circumsporozoite Protein

Abstract: A malaria vaccine that elicits long-lasting protection and is suitable for use in endemic areas remains urgently needed. Here, we assessed the immunogenicity and prophylactic efficacy of a vaccine targeting a recently described epitope on the major surface antigen on Plasmodium falciparum sporozoites, circumsporozoite protein (CSP). Using a virus-like particle (VLP)-based vaccine platform technology, we developed a vaccine that targets the junctional region between the N-terminal and central repeat domains of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Although the junctional and minor repeat regions of PfCSP are known to be sites of neutralization due to mAb characterization [ 31 , 32 , 34 ], this result is one of the first demonstrations that peptides spanning these epitopes could elicit neutralizing antibodies. The data presented here are in agreement with a recent study by Jelinkova et al, which showed that peptide 21 elicited partial protection when displayed on Qβ bacteriophage VLPs [ 48 ]. Similarly, a tetra-branched peptide covering the junctional region has been shown to reduce liver burden following mosquito bite challenge [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the junctional and minor repeat regions of PfCSP are known to be sites of neutralization due to mAb characterization [ 31 , 32 , 34 ], this result is one of the first demonstrations that peptides spanning these epitopes could elicit neutralizing antibodies. The data presented here are in agreement with a recent study by Jelinkova et al, which showed that peptide 21 elicited partial protection when displayed on Qβ bacteriophage VLPs [ 48 ]. Similarly, a tetra-branched peptide covering the junctional region has been shown to reduce liver burden following mosquito bite challenge [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, CHIK-p21-23 N /p21-23 B elicited higher titers against the NANP major repeats and lower responses to the junctional and minor repeat epitopes, more closely resembling mAbs like 317, which are cross-reactive but have preferred binding to the major repeats. These data lend credence to the idea that eliciting cross-reactivity across the various epitopes in the repeat region may be the best strategy to induce protection [ 48 , 50 ]. Interestingly, CHIK-p21-23 N /p21-23 B does not display the “NPNA” structural motif bound by mAbs targeting the major repeats [ 26 , 51 ].…”
Section: Discussionmentioning
confidence: 55%